DISCRETE TIME DYNAMICS OF AN OCEAN ECOSYSTEM - Sayliyeva, Gulrux R. (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
For a discrete-time dynamical systemgenerated by a of nonlinear operator ocean ecosystem we investigate the set of limit points of its trajectories. Keywords: Quadratic stochastic operator, Volterra operator, ecosystem modeling